ANALISIS MINAT KUNJUNGAN KEMBALI TAMU SANGKAN RESORT AQUA PARK PADA AKHIR PANDEMI COVID-19 - Yulius, Kevin Gustian; Ferdela Fernandez; Yosep Dudedes Timba (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
This study aims to analyze the factors that influence revisit intention to Sangkan Resort Aqua Park at the end of the COVID-19 pandemic. This research is an explanatory research with quantitative data collected through questionnaires. Results of the validity and reliability tests show that the research instrument is valid and reliable. The results of data analysis show that only the fulfillment variable has a significant influence on the guest's revisit intention. Physical environment, social environment, and price variables do not have a significant effect partially, but simultaneously these four variables have a significant influence on the guest's revisit intention. The coefficient of determination shows that the independent variable can only explain about 24.4% of the variation in intention to return. These findings can provide insight for the hospitality industry at Sangkan Resort Aqua Park to improve service quality and competitiveness. Hotel managers can focus more on meeting guest needs to increase interest in return visits. In addition, this research also contributes to scientific knowledge in the hotel and tourism industry. The results of this research can be used as a reference for developing tourism policies at the regional and national levels and helping local economic growth after the pandemic ends.